Viden og kampen om det virkelige - Bjerre, Jørn; Allesøe, Bo (Academic Quarter | Akademisk kvarter, 2018)
In this final article we will reflect on the contributions to this volume, relating these to positions within philosophy of science, realism, constructivism, critical and social realism, and discuss relativism and critique of ideology as well. The article commences by examining a battle of what is to be understood as the real currently underway in politics and everyday life. Subsequently, the article tries to show how a parallel battle takes place in philosophy of science.